Patriot Team and Their Role on Stressing the Number of Street Crimes in Bekasi City - Chidmad Chudori (Police Studies Review, 2021)
This research was motivated by the high number of street crimes in the midst of the covid-19 pandemic, then the Bekasi City Metro Police Patriot Team was re-established in March 2020 to reduce the number of street crimes. The Patriot Team is a special team formed to reduce crime rates in the Bekasi City Metropolitan Police Legal Area. Therefore, a study was conducted that aims to describe the performance of the Patriot Team Polres Metro Bekasi City which has succeeded in reducing crime rates, especially street crimes, but behind this success there are several shortcomings that can be improved to be better. This study uses several theories and concepts, namely the Performance Concept, the Patrol Concept, the Countermeasure Theory and the Management Theory. The research was conducted with a qualitative approach, using descriptive analytical research methods, as well as data collection techniques by interviewing, observing and reviewing documents. Researchers in this case only discuss 4 (four) types of street crimes, namely brawls, theft with violence, theft with weights and illegal racing. Researchers only discuss 4 (four) street crimes that are the most prominent in the Bekasi City Police Station and become the main priority. Later in the study it was found that there were several places marked as areas where these street crimes occurred and every night the Patriot Team patrolled the areas that had been mapped. The decrease in the number of street crimes was not only due to the hard work of the Patriot Team, but there was assistance from the television media and social media which covered the activities and disseminated it so that it had a fearful effect on the community, this can be studied using the deterrence theory that the researchers included in this study. However, there are shortcomings in the administration, because after all, administration is very important in this Polri institution. Based on the results of the study, the researchers suggest that the Bekasi Metro Police Chief should fix the administration of the Patriot Team and provide additional personnel to support the performance of the Bekasi City Metro Police Patriot Team to be even better in the future.